2011
DOI: 10.2108/zsj.28.517
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Subtypes of Serotonin Receptors in the Feeding Circuit of a Pond Snail

Abstract: In the central nervous system of the pond snail Lymnaea stagnalis, serotonergic transmission plays an important role in controlling feeding behavior. Recent electrophysiological studies have claimed that only metabotropic serotonin (5-HT(2)) receptors, and not ionotropic (5-HT(3)) receptors, are used in synapses between serotonergic neurons (the cerebral giant cells, CGCs) and the follower buccal motoneurons (the B1 cells). However, these data are inconsistent with previous results. In the present study, we th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…However, we do know that food deprivation causes a number of physiological changes in snails. For example, serotonin (5-hydroxytryptamine: 5-HT), a multimodal transmitter, controls both feeding and cardiovascular behaviors in snails (Kemenes et al, 1989;Buckett et al, 1990;Hatakeyama and Ito, 1999;Yamanaka et al, 2000;Kawai et al, 2011). Recently, Yamagishi and colleagues found that food deprivation significantly alters heart rate in Lymnaea .…”
Section: Discussionmentioning
confidence: 99%
“…However, we do know that food deprivation causes a number of physiological changes in snails. For example, serotonin (5-hydroxytryptamine: 5-HT), a multimodal transmitter, controls both feeding and cardiovascular behaviors in snails (Kemenes et al, 1989;Buckett et al, 1990;Hatakeyama and Ito, 1999;Yamanaka et al, 2000;Kawai et al, 2011). Recently, Yamagishi and colleagues found that food deprivation significantly alters heart rate in Lymnaea .…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of these microelectrodes ranged from 50 to 70 MΩ. We intracellularly recorded a compound EPSP in the B1 motor neuron that was evoked by bursting action potentials in the CGC [28]. The constant depolarizing current was injected into the CGC for 1 s to elicit the bursting action potentials using the amplifier's built-in function for current injection.…”
Section: Methodsmentioning
confidence: 99%
“…The serotonergic EPSP in the B1 motor neuron is mediated via at least two types of serotonin receptors: metabotropic 5-HT 2 -like receptors and ionotropic 5-HT 3 -like receptors (Kawai et al, 2011). The fast component of compound EPSP is mediated by 5-HT 3 -like receptors, and the slow component is generated via 5-HT 2 -like receptors.…”
Section: Results and Discussion Contribution From A Presynaptic Neuromentioning
confidence: 99%
“…Insulin may evoke a rapid recruitment of functional GABA A receptors to the postsynaptic membrane, suggesting a fundamental mechanism for the generation of synaptic plasticity. At the CGC-B1 synapses in L. stagnalis, serotonin appears to be the likely transmitter substance (Kawai et al, 2011), so it is possible that MIPs could result in an increase in serotonin receptors (possibly ionotropic 5-HT 3 -like receptors) on the B1 motor neurons. This possibility is currently being examined.…”
Section: Possible Function Of Insulin In a Long-term Synaptic Enhancementioning
confidence: 99%